Valuing visitor’s willingness to pay for green tourism conservation: A case study of Bukit Larut Forest Recreation Area, Perak, Malaysia - Fazilah Musa; Rutthiradevi Nadarajah (Taylor & Francis, 2023)
Bukit Larut, previously known as ‘Maxwell Hill’, is declared a Forest Recreation Area as part of green infrastructure that enhances the quality of life of people and boosts green tourism. However, due to the lack of a market, it is difficult to quantify the economic value of green tourism in monetary terms for these resources. Using the Contingent Valuation Method (CVM), this study aims to determine the willingness to pay (WTP) for green tourism conservation in the Forest Recreation Area of Bukit Larut, Perak. In this study, a total of 250 respondents were collected via a questionnaire distributed at random. This study assigned five different bid prices, MYR5, MYR10, MYR15, MYR20, and MYR25. The Logit Model estimates the visitor’s WTP for green tourism conservation. This study indicates that most visitors are willing to pay a certain amount for green tourism conservation, driven by race, religion, age, marital status, education level, and income. Regression analysis showed that the estimated mean visitor will-ingness to pay is MYR 4.69, whereas the median WTP is MYR 3.68. Therefore, it was determined that Bukit Larut’s conservation initiatives were viable for future green tourism. The financial resources would assist the management in allocating funds for conservation and maintenance.